Analisis Kepuasan Konsumen Terhadap Kualitas Pelayanan Citanaya Titip Barang dengan Metode Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA) - Zakaria, Sakina; Basuki, Gatot (Institut Teknologi Adhi Tama Surabaya, 2024)
Citanaya Titip Barang is a service business specializing in parcel storage and delivery from Surabaya to Ende, East Nusa Tenggara, with a primary focus on customer satisfaction and time delivery, This research aims to analyze customer satisfaction towards the service quality of Citanaya Titip Barang using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The study reveals a customer satisfaction index of 0.87, falling within the CSI scale of 0.81-1.00, indicating high satisfaction with service attributes developed through open questionnaires. Key attributes to maintain include neat and professional packaging, proactive notifications regarding delivery status, and other attributes identified in IPA's Quadrant B. Additionally, areas for improvement include the ability to provide flexible delivery schedules and an online tracking system. The implications of these findings serve as a foundation to improve service quality and strengthen customer relationships amidst dynamic consumer needs and competition in the logistics industry.